Preparation of 3D printed silicon nitride bioceramics by microwave sintering - Xiaofeng Zeng; Coswald Stephen Sipaut @ Mohd Nasri; Noor Maizura Ismail; Yuandong Liu; Yan Yan Farm; Bo Peng; Jiayu He (Elsevier B.V., 2024)
Silicon nitride (Si₃N₄) is a bioceramic material with potential applications. Customization and high reliability are the foundation for the widespread application of Si₃N₄ bioceramics. This study constructed a new microwave heating structure and successfully prepared 3D printed dense Si3N4 materials, overcoming the adverse efects of a large amount of 3D printed organic forming agents on degreasing and sintering processes, further improving the comprehensive performance of Si₃N₄ materials. Compared with control materials, the 3D printed Si₃N₄ materials by microwave sintering have the best mechanical performance: bending strength is 928 MPa, fracture toughness is 9.61 MPa·m1/2. Meanwhile, it has the best biocompatibility and antibacterial properties, and cells exhibit the best activity on the material surface. Research has shown that the excellent mechanical performance and biological activity of materials are mainly related to the high-quality degreasing, high cleanliness sintering environment, and high-quality liquid-phase sintering of materials in microwave environments.